Treatment of single maxillary gingival recession associated with non-carious cervical lesion: Randomized clinical trial comparing connective tissue graft alone to graft plus partial restoration - Santamaria, Mauro Pedrine [UNESP]; Silveira, Camila Augusto [UNESP]; Mathias, Ingrid Fernandes [UNESP]; Silva Neves, Felipe Lucas da [UNESP]; Santos, Lucio Murilo dos [UNESP]; Neves Jardini, Maria Aparecida [UNESP]; Tatakis, Dimitris N.; Sallum, Enilson Antonio; Bresciani, Eduardo [UNESP] (Wiley-Blackwell, 2018)
BackgroundGingival recession (GR) is frequently associated with non-carious cervical lesion (NCCL) forming a combined defect (CD). The aim of this study was to evaluate a new multidisciplinary protocol for CDs. MethodsForty patients presenting 40 Miller's Class I or II GR defects associated with B+ tooth cervical defect were randomly allocated to one of the following treatments: test group (n=20), partial restoration (PR) of the NCCL, in which the apical border of the restoration was placed 1mm beyond the cement-enamel junction estimation, and connective tissue graft (CTG+PR) and Control Group (n=20), odontoplasty of the NCCL and connective tissue graft (CTG). Clinical, aesthetic and patient-centred outcomes were evaluated. ResultsAfter 12months, CD coverage rates were 75.3% (2.51.0mm) for CTG+PR and 74.6% (2.4 +/- 1.1mm) for CTG (p>0.05). The estimated complete root coverage was 60% (n=12) for CTG+PR and 70% (n=14) for CTG. CTG+PR resulted in significantly better dentin hypersensitivity (DH) reduction (p=0.034). Both groups resulted in aesthetic improvements; however, the CTG+PR group showed better gingival contour results. ConclusionsCTG and CTG+PR were effective to treat CD. Use of PR resulted in better gingival margin contour and DH reduction, without effect on CD coverage by CTG. (NCT02817763).
Keywords: dental esthetics; dentin sensitivity; gingival recession; tooth abrasion